Challenges in Bootstrapping a Start-Up Venture: Keenga Research Turning the Tables on Venture Capitalists - Prescott C. Ensign; Anthony A. Woods (Journal of Entrepreneurship, Management and Innovation)

(untitled)
This case study chronicles the timeline of a new venture – Keenga Research. Keenga Research has a novel proposition that it is seeking to introduce to the market. The business concept is to ask entrepreneurs to review the venture capital (VC) firm that funded them. Reviews of VC firms would then be developed and marketed to those interested (funds and perhaps enterprises seeking funding). What makes this case unique is that Keenga Research was a lean start-up. Bootstrapping is a situation in which the entrepreneur chooses to fund the venture with his/her own personal resources. It involves self-funding (family and friends), tight monitoring of expenses, and maintaining control of ownership and management (Winborg & Landstrom 2001; Perry, Chandler, Yao, & Wolff, 2011; Winborg, 2015). The lean start-up approach favors experimentation over elaborate planning, customer feedback over intuition and iterative design over traditional big upfront research and development. This case study requires the reader to consider a number of the basic challenges facing all entrepreneurs and new ventures. Is the concept marketable? Can the concept be developed and brought to market in a timely manner? Will the product generate revenue? How? When? What are the commitments of the entrepreneurs? Have they considered the major challenges to be faced? Since this venture involved gathering and developing research information and then creating an online platform, Keenga Research faced significant concept-to-market challenges. The research method used in this case study is first person participant observation and interviews. One of the authors was a team member so the contextual details come from direct observation and first-hand knowledge. This method of research is often used in anthropology, sociology, and social psychology where an investigator studies the group by sharing in its activities. The other author provided an objective and conceptual perspective for analyzing the venture. This combination of perspectives provides a more balanced picture.